The Expansive Domain of Rule of Law: Arguing from the International Legal Framework - Bandopadhay, Somabha (Christ University Law Journal, 2022)
Rule of law binds the humankind together, or at least, it is expected to do so. In an attempt to keep the sanctity of the UN Charter the San Francisco conference and the visions which made way for the modern contemporary world, rule of law is the quintessential word. But, have there been any realization on the importance of the principle with regard to the international legal regime is the question that propels thoughts. Indeed, since the conception of the idiom of rule of law, there have been enormous scholarly explorations on the nuances of it, this question is the domain the authors in this article attempts to undertake. With a holistic journey of the principle and how the practical implications of the same are felt across different sectors of the mechanisms of law, the authors investigates this question in depth. Be it in the international setting or the domestic set-up with the UN framework the case of the former have found predominance and the Indian and Singaporean experiences haven been exemplified in the latter, the author outlines the significance of rule of law at work. The novelty of the paper lies in the critical analysis of how international human rights finds expression through this at the same time bolstering the notion of rule of law and how ultimately they are mutually interrelated to each other. The paper also attempts to answer some basic questions on the administrators of rule of law at this international legal platform, the instruments propelling rule of law and explores the human rights dimension at play concerning this. On this pivotal underlying element of the critical role of human rights law in this discourse, the author has assessed the international human rights framework comprehensively as against the rule of law which otherwise is a broad ambit to place reliance upon and with the amplitudes of international judicial structures and legislative materials coupled with important legal principles and doctrines of international law, the author has evaluated the rule of law to present how multifarious the doctrine of rule of law could be which even though was initially conceived for the domestic jurisdictions have become important for the universal jurisdiction whose relevance can never be undermined.